"Unemployment among Libyan Graduates and its Relationship to Future jop Satisfaction" (Comprehensive Journal of Science, 2026)
To analyze the relationship between Unemployment among Libyan  This study aimsuniversity  graduates  and  their xpectations  of  future job satisfaction ,in light of  theChallenges  faced  by the labor market  and  its inability  to absorb The  in creasing..The study  assumes that  continued  unemployment Does not only affect theindividuals economic situation, but also influences psychological  and  social    attitudes, especially regarding the evaluation  of upcoming  professional    opportunities. The study adopted  the  descriptive . analytical  approach  and reliedTheoretically  on  Expectancy  Theory  to  explain how perceptions of Jop satisfaction  are formed  in  light  of  available  opportunities . It Focused  on measuring  the    impact  of  unemployment duration, field of study , and opportunities for training   and   qualific ation  in  determining  the  expected  level  of  satifaction. The most important  findings revealed  an  inverse  relationship Between  unemployment and future job satisfaction. The longer  the Period  of  unemployment and the weaker the chances  of  obtaining Asuitable  job, the lower the graduates,professional     expectations  and Satisfaction. The results also showed that training  and  qualification Can contribute  to enhancing  optimism and improving  future    Perceptions.
Keywords: Unemployment . University Graduates . Future Job Satisfaction . Career Expectations . Libya